A LOT OF WAYS OF WEDDING TRADITIONS DIFFER AROUND THE WORLD - Egamberdiyeva Iroda; Ergasheva Feruza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The marriage ceremony serves as an honour and dignity to the couple and their families. In the eyes of the people, the couple is responsible. They are ready to take up responsibilities in marriage, this gives them social recognition and dignity in society. Marriage is not only between the couple but rather between the two families. The ceremony together unites the families of the couple. They share every moment of joy and get to know each other. In recent times, there are marriages across tribes and regions so the ceremony brings tribes and ethnic groups together and promotes peace and unity between the two tribes which inures to the nation at large. In this article There are some basic information about International unusual wedding planning around the world.